2013
DOI: 10.1016/j.ydbio.2013.07.028
|View full text |Cite
|
Sign up to set email alerts
|

A core transcriptional network composed of Pax2/8, Gata3 and Lim1 regulates key players of pro/mesonephros morphogenesis

Abstract: Translating the developmental program encoded in the genome into cellular and morphogenetic functions requires the deployment of elaborate gene regulatory networks (GRNs). GRNs are especially crucial at the onset of organ development where a few regulatory signals establish the different programs required for tissue organization. In the renal system primordium (the pro/mesonephros), important regulators have been identified but their hierarchical and regulatory organization is still elusive. Here, we have perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…BMP signals are essential for MD specification by regulating Pax2 expression Previous studies reported that Lim1 acts downstream of Pax2 in several developmental contexts, including the development of mouse pronephros (Boualia et al, 2013;Bouchard et al, 2002). We therefore investigated whether Pax2 expression in the MFR was required for the expression of Lim1 during MD development.…”
Section: Expression Of Pax2 Lim1 and N-cadherin During MD Specificationmentioning
confidence: 99%
“…BMP signals are essential for MD specification by regulating Pax2 expression Previous studies reported that Lim1 acts downstream of Pax2 in several developmental contexts, including the development of mouse pronephros (Boualia et al, 2013;Bouchard et al, 2002). We therefore investigated whether Pax2 expression in the MFR was required for the expression of Lim1 during MD development.…”
Section: Expression Of Pax2 Lim1 and N-cadherin During MD Specificationmentioning
confidence: 99%
“…Recent studies have explored the gene regulatory networks downstream of Pax genes in the renal system. In the nephric duct, Pax2/8 were found to regulate the transcription factor genes Gata3 and Lhx1, which together with Pax proteins, turn on the downstream transcriptional program necessary for renal morphogenesis ( Figure 2) [50]. Gata3 acts as a driver of nephric duct guidance and morphogenesis in the mouse embryo [51], while Lhx1 plays an M a n u s c r i p t important role in nephric duct elongation and survival [52][53][54][55].…”
Section: Pax Gene Activity In Pro/mesonephros Morphogenesismentioning
confidence: 99%
“…Gata3 acts as a driver of nephric duct guidance and morphogenesis in the mouse embryo [51], while Lhx1 plays an M a n u s c r i p t important role in nephric duct elongation and survival [52][53][54][55]. Among the key developmental regulators acting downstream of the Pax2/8-Gata3-Lhx1 gene regulatory core [50] are effector genes such as Emx2 [56], Hnf1 [57] and Plac8 [50] ( Figure 2). Emx2 expression is regulated by Pax2 and is involved in a positive feedback loop that maintains Pax2 expression in the nephric duct and ureters [58].…”
Section: Pax Gene Activity In Pro/mesonephros Morphogenesismentioning
confidence: 99%
See 2 more Smart Citations